The Correlation Between Internet Addiction and Interpersonal Relationship Among Teenagers and College Students Based on Pearson's Correlation Coefficient: A Systematic Review and Meta-Analysis - Hao, Qing-hong; Peng, Wei; Wang, Jun; Tu, Yang; Li, Hui; Zhu, Tian-min (Frontiers in Psychiatry, 2022)
Background: Internet addiction (IA) has become a serious social issue, induced troubles in interpersonal relationship, which may negatively impact the healthy development of teenagers and college students. Thus, current research aimed to synthesize the available evidence to clarify the correlation between IA and troubles in interpersonal relationship. Method: We searched eight electronic databases from inception to December 2020. Study quality was assessed by the Newcastle-Ottawa Scale (NOS), and Agency for Healthcare Research and Quality (AHRQ). We analyzed the data by extracting the Pearson correlation coefficients of each study and converted it into Fisher’s Z. Pooled r was conducted by Fisher’s Z and standard error (SE). STATA (Version 15.0) software was used for data synthesis. Results: A total of 10,173 literatures were initially identified, and 26 studies (n=14,638 participants) were retrieved for further analysis. The results indicated that there was a significant positive correlation between IA and interpersonal relationship troubles [0.36 (95% CI 0.35-0.38)]. In addition, there was a positive correlation between IA and different dimensions of interpersonal relationship reflected by troubles with interpersonal conversation, making friends, dealing with people and heterosexual communication, with the result of [0.26 (95% CI 0.18-0.33)], [0.29 (95% CI 0.20-0.37)], [0.27 (95% CI 0.19-0.34)], [0.22 (0.15-0.30)], respectively. The Egger’ test suggested that there was no publication bias (P>0.05). Conclusion: IA is positively correlated with troubles in interpersonal relationship. This research will provide new idea and direction for further intervention, clinical therapy and policy-making of IA to some extent.